To register emotions at school, a social and educational need (2013)
Traditionally, emotions have played a very discreet role in the school and affectivity in the classroom has been lacking in the relationships of teachers and students. With all of the above, since Mayer &amp, Salovey (1990) first coined the term Emotional Intelligence (EI) in an academic journal, the number of researches and findings regarding the relationship of EI with different behaviors, with life success and academic achievement among others, have led to important progress, allowing repositioning of emotional management programs in educational institutions. It should be noted that various disciplines such as Psychology, Affective Neuroscience, Buddhism and Education, have given prominence to emotions and their impact on social and human development. For this reason we can identify several successful experiences in different educational contexts that have nurtured these findings, besides suggesting a focus for the development of emotional skills in teachers ‘trainee.